Impact Of Control Augmentation On Pilot Workload During Shipboard Helicopter Hover Operation - Kalra, A.; Greiwe, D. H. (My University, 2025)
The integration of control augmentation techniques into helicopter systems aims to assist pilots during the critical phases of shipboard operations to mitigate the effects of ship motion, wind and other environmental factors that can compromise safety. The control augmentation presented in this paper involves the implementation of model following control laws featuring a combination of advanced response types with hold modes to improve helicopter handling qualities. The paper introduces a translational rate command type, relative to the ship, which incorporates Velocity Hold and Position Hold features to assist pilots and automate various stages of the ship deck landing maneuver. An Attitude Command Attitude Hold has been used as a baseline response type for the comparison. A preliminary pilot evaluation of the proposed control laws during a hover operation is presented to assess the impact of control augmentation on the pilot workload, task performance and operational safety. In addition to quantitative task performance data and qualitative pilot rating scales, eye tracking glasses were used as an additional metric to record pilot gaze data providing insights into attention distribution and cognitive demand across different control strategies. Simulation results demonstrate that the implemented control augmentation techniques enable a stabilised hover relative to ship, while also contributing to reduced workload, improved task performance and increased overall safety perception for the pilots.